ASOSIASI JENIS BURUNG DENGAN VEGETASI HUTAN MANGROVE DI WILAYAH PESISIR PANTAI KECAMATAN TINOMBO SELATAN KABUPATEN PARIGI MOUTONG - Malindu, Faizan Dg; Labiro, Elhayat; Ramlah, Sitti (Universitas Tadulako, 2016)
Indonesia has tropical areas which part of oriental region in the division of the world's major biomes. Generally, human holds that certain species are useful when they are able to meet their own needs indirectly, such as food sources, clothing or any other needs.Â Frequently, this limited view makes utilization effort and conservation runs into barriers.Â Thus, to overcome these barriers, human view needs to be expanded and it should be instilled the awareness for understanding that the presence of any species have benefits and roles in environmental life. Bird is one of various species of wildlife which is easy to find because it spreads widely in every type of ecosystem. The aim of this study is to determine Bird Species Association with Mangrove Vegetation in Coastal Marine Territory in South Tinombo Sub-District of Parigi Moutong District. The research method applied are primary data and secondary data collection which the primary data is obtained through observation types, attendance, or presence time (direct observation in the field) while the secondary data is obtained from office, related agencies and previous studies reports. The technique of data collection is to create a compartment 20 x 20 m totally 20 switch and they are placed along the path transek with 500 meters length. The result shows that from 16 birdsâ€™ species and 4 types of mangroves found from each plot observations, there are only two bird species which have association with mangrove namely Red Turtle Dove and Collared Kingfisher with Rhizophora mucronata. Those are located in Tinombo South Sub-district.Keywords: Bird Species Association with Mangrove.